Nestedness structure of bird assemblages in a fragmented forest in Central Argentina: the role of selective extinction and colonization processes - Dardanelli, Sebastian; Bellis, Laura Marisa (BIOEXPLORA, 2021)
Nestedness structure of bird assemblages in a fragmented forest in Central Argentina: the role of selective extinction and colonization processes. Nestedness analysis constitutes an important tool to understand the processes that shape wildlife communities. It also allows a quick first evaluation of species extinction proneness in fragmented landscapes. Here, we tested whether avian assemblages in the fragmented Espinal forest exhibited nested subset patterns. Furthermore, we examined whether selective extinction or selective colonization are driving nested subset patterns. We studied avian assemblages in 13 forest fragments in central Argentina during breeding and non–breeding seasons. We completed partial Spearman rank correlations to explore the relationship between nestedness rank order and habitat patch variables and species life history traits related to species extinction proneness and colonization rate. Bird species showed strong nestedness patterns, both for the total incidence matrix and for forest fragments and species separately. Nestedness patterns were similar during the breeding and non–breeding seasons. The nested rank order of forest fragments correlated with area and distance to nearest fragment, both of which are patch characteristics known to increase the probabilities of species extinction. The nested rank order of species was correlated with the minimum area of species requirement, trophic guild, and range size, traits that are linked to extinction risk. Selective extinction processes rather than selective colonization appear to be driving nestedness patterns of bird assemblages in fragmented Espinal forest. The most effective way to preserve forest bird species in the Espinal forest seems to be by protecting the larger fragments of this relictual forest.